Hot deformation behavior and processing map of Nb-V-Ti micro-alloyed steel. (2020) - Kant Thakur, Suman; Harish, Ladi; Kumar Das, Alok; Rath, Sushant; Pathak, P.; Kumar Jha, Bimal
Abstract: Optimization of process parameters during plate rolling of micro-alloyed steel plays an important role in achieving the stipulated mechanical properties. The hot deformation behaviour of Nb-V-Timicro-alloyed steel was studied to determine safe region during plate rolling and to achieve high strength (>450 MPa) defect free plates. The hot flow behaviour of experimental steel was studied with a Gleeble-3500 thermo-mechanical simulator, at 850–1100°C, 1–100 s-1. The constitutive equations of the experimental steel was established using Arrhenius equations and material constants were evaluated at different strains. Model too predict the flow stress was developed by establishing its relation with strain, strain rate and deformation temperature using multivariable optimization technique based on parameter estimation methodology. The processing map based on Dynamic Materials Model (DMM) was constructed to evaluate the hot workability of experimental micro-alloyed steel and identify the safe region for hot deformation. The processing maps of the experimental steel show a region of instability at temperature < 900 °C and when strain rate is > 1 s −1 and this domain needs to be avoided during hot deformation.